O direito à educação básica no Brasil e o problema do seu financiamento - Freitas, Aline da Silva (2009)
The history of the right to basic education in Brazil and the analysis of the legal ordenament in force demonstrate positive evolution in its protection and effectiveness. It is important because this is the education level is directed to the commom formation indispensable to the citizenship, to the self development and the improvement of ways to progress in labor and in subsequent studies. Despite that, there are barriers for this happen, in special the financial, without there is not how to assure the effectiveness of the basic education right. The Republic Constitution of 1988 determined percentage of the tax income to the maintenance and development of education, with emphasis on the fundamental education. However, the successive politics of resources application are yet insufficient and do not have the imperative characteristic of continuity. The expectative is that with the Fundeb , fund of countable nature to the maintenance and development of the basic education and the teaching valorization, implemented in 2007 and to be apply until 2020, changes will occur, in special the diminution of the regional inequality, establishing the minimum level to the universalization with quality of the education object of this study. The problem is that there is not public transparency on divulging data about its implementation yet and the citizens do not have mechanism to control it directly. The State cannot exempt from its responsibility, in truth, the basic education is included on the minimum existential idea.